2018
DOI: 10.2147/opth.s153717
|View full text |Cite
|
Sign up to set email alerts
|

Scleral buckling in the management of rhegmatogenous retinal detachment: patient selection and perspectives

Abstract: Although the technique of pars plana vitrectomy (PPV) develops rapidly, scleral buckling (SB) has several advantages over PPV for rhegmatogenous retinal detachment (RRD), including early visual rehabilitation and prevention of cataract progression. It is recommended to select the primary procedure for RRD by considering the advantages and disadvantages of each procedure based on the patient status. The vitreous body status affects the features of RRD. Vitreous liquefaction is an age-dependent process, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 61 publications
3
62
1
2
Order By: Relevance
“…Scleral buckle technique possesses some clear advantage over vitrectomy by being an extraocular surgery and a preferred technique for young phakic patients 5. A comparison of the SB vs primary vitrectomy in RRD study (SPR) showed in the subgroup analysis that phakic patients had better visual outcomes, less cataract progression, and needed fewer retina-affecting procedures in the SB group compared with the vitrectomy group 6.…”
Section: Discussionmentioning
confidence: 99%
“…Scleral buckle technique possesses some clear advantage over vitrectomy by being an extraocular surgery and a preferred technique for young phakic patients 5. A comparison of the SB vs primary vitrectomy in RRD study (SPR) showed in the subgroup analysis that phakic patients had better visual outcomes, less cataract progression, and needed fewer retina-affecting procedures in the SB group compared with the vitrectomy group 6.…”
Section: Discussionmentioning
confidence: 99%
“…Since first introduced by Machemer in 1971, pars plana vitrectomy (PPV) has been shown to be an effective management option for rhegmatogenous retinal detachment (RRD) 1–3. Although scleral buckling is preferred in some specific situations,4,5 PPV is now generally accepted as the primary procedure for management of RRD. The most commonly used techniques consist of PPV, barrier laser photocoagulation, and the use of vitreous tamponade.…”
Section: Introductionmentioning
confidence: 99%
“…Scleral buckling, which requires the surgeon to sew a silicone strip or sponge to the outside of the eye, was first introduced in the 1950s and had been the standard method used for treating RRD for several decades. 8 , 9 Although the application of PPV has significantly increased and become the most commonly used procedure, even with the evolution of vitrectomy machines and related instruments, 9 16 pars plana vitrectomy surgery still has disadvantages, such as the acceleration of cataracts in phakic eyes, a lower initial rate of anatomical success, increased risk of proliferative vitreoretinopathy and an epiretinal membrane, and a higher cost. 8 , 17 21 However, scleral buckling is an extraocular procedure, does not require that a posterior vitreous detachment be present, and does not promote cataract formation; so, it still has some merits and continues to play an important role in retinal reattachment surgery.…”
mentioning
confidence: 99%
“… 8 , 9 Although the application of PPV has significantly increased and become the most commonly used procedure, even with the evolution of vitrectomy machines and related instruments, 9 16 pars plana vitrectomy surgery still has disadvantages, such as the acceleration of cataracts in phakic eyes, a lower initial rate of anatomical success, increased risk of proliferative vitreoretinopathy and an epiretinal membrane, and a higher cost. 8 , 17 21 However, scleral buckling is an extraocular procedure, does not require that a posterior vitreous detachment be present, and does not promote cataract formation; so, it still has some merits and continues to play an important role in retinal reattachment surgery. 22 30 Indeed, PPV surgery will remain an ideal treatment option in selected cases, especially in patients who are younger, in phakic eyes, and in limited retinal detachment, particularly with a hole in the lattice or an inferior location, even in subjects with high myopia.…”
mentioning
confidence: 99%
See 1 more Smart Citation